Pravastatin reduces plasma levels of extracellular vesicles in pregnancies at high risk of term preeclampsia - Santoyo, Jean Michell; Noguera, José Antonio; Avilés, Francisco; Hernández-Caselles, Trinidad; de Paco-Matallana, Catalina; Delgado, Juan Luis; Cuevas, Santiago; Llinás, M. Teresa; Hernández, Isabel (Frontiers in Pharmacology, 2023)
Elevated plasma levels of extracellular microvesicles have been associated with impaired placentation, angiogenesis imbalance, intravascular inflammation and endothelial dysfunction in women with preeclampsia, thus suggesting that circulating microvesicles may be a good therapeutic target for the treatment of the disease. Recently, statins have been considered as a potential treatment for the prevention of preeclampsia because of their pleiotropic effects, including improvement of endothelial dysfunction and inhibition of inflammatory responses. However the effects of these drugs on circulating microvesicles concentration in women at risk of preeclampsia have not been established. We aimed to assess the effects of pravastatin on circulating microvesicles generation in women at high risk of term preeclampsia. In a sample of sixty eight singleton pregnant women participating in the multicenter, double-blind, placebo-controlled STATIN trial (Nº EducraCT 2016-005206-19 ISRCTN), thirty-five women received placebo and thirty-three women received a 20 mg/day dose of pravastatin for approximately three weeks (from 35-37 weeks of gestation until delivery). Microvesicles were characterized and quantified by flow cytometry using annexin V and cell specific antibodies directed against platelets, endothelial, leukocyte and syncytiotrophoblast cell surface markers. In placebo treated women, a significant increase in plasma levels of extracellular microvesicles from platelets (34% p<0.01), leukocytes (33% p<0.01), monocytes (60% p<0.01), endothelial cells (40% p<0.05) and syncytiotrophoblast (22% p<0.05) were observed. However, treatment with pravastatin produced a significant reduction of plasma extracellular microvesicles from platelets (42% p<0.001), leukocytes (25% p<0.001), monocytes (61% p<0.001), endothelial cells (69% p<0.001), activated endothelial cells (55% p<0.001) and syncytiotrophoblast (44% p<0.001). These results indicates that pravastatin reduces activated cell-derived membrane vesicles from the maternal vasculature, blood and placental syncytiotrophoblast of women at high risk of term preeclampsia, suggesting that this statin may be beneficial in reducing endothelial dysfunction, pro-inflammatory and pro-coagulatory states characteristics of the disease.